2013
DOI: 10.1002/ejsp.1963
|View full text |Cite
|
Sign up to set email alerts
|

Less is more: The effect of multiple implementation intentions targeting unhealthy snacking habits

Abstract: Implementation intentions have been shown to effectively change counter‐intentional habits. Research has, however, almost solely been concerned with the effectiveness of a single plan. In the present research, we investigated the behavioral and cognitive implications of making multiple implementation intentions targeting unhealthy snacking habits and its underlying processes, linking multiple habitual snacking cues to healthy alternatives. Study 1 revealed that formulating multiple implementation intentions wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 52 publications
5
35
0
Order By: Relevance
“…healthy snacks when forming any type of II (regardless of match with their regulatory orientation), while participants with strong unhealthy snacking habits consumed more healthy snacks only when forming II that matched their regulatory orientations (promotion-focused or orientation-focused). Verhoeven and colleagues (2013) investigated the effectiveness of making a single versus multiple II for reducing unhealthy snacking habits, as measured by the Self-Report Habit Index (Verhoeven et al, 2013). Findings showed that a single plan successfully reduced unhealthy snacking habits, whereas formulating multiple II was ineffective.…”
Section: Resultsmentioning
confidence: 99%
“…healthy snacks when forming any type of II (regardless of match with their regulatory orientation), while participants with strong unhealthy snacking habits consumed more healthy snacks only when forming II that matched their regulatory orientations (promotion-focused or orientation-focused). Verhoeven and colleagues (2013) investigated the effectiveness of making a single versus multiple II for reducing unhealthy snacking habits, as measured by the Self-Report Habit Index (Verhoeven et al, 2013). Findings showed that a single plan successfully reduced unhealthy snacking habits, whereas formulating multiple II was ineffective.…”
Section: Resultsmentioning
confidence: 99%
“…These findings may be interpreted as an indication that the increased automaticity associated with the exercise habit has freed self‐regulatory capacity that participants could use to more effectively regulate other desirable health behaviours. This is also the hypothesised mechanism behind many interventions involving the formulation of one or more action plans (or implementation intentions) which are hypothesised to facilitate behaviour change by increasing the automaticity of behavioural performance (de Bruijn, Wiedemann, & Rhodes, ; Sheeran, Webb, & Gollwitzer, ; Verhoeven, Adriaanse, de Ridder, de Vet, & Fennis, ; Wiedemann, Lippke, & Schwarzer, ). Evaluated in a multiple‐behaviour paradigm, the known mechanisms of planning interventions can be contrasted against a competing hypothesis, that planning increases the salience and priority of certain behaviours over that of alternative options.…”
Section: Overall Discussionmentioning
confidence: 99%
“…Third, findings from the literature regarding the effectiveness of making multiple implementation intentions on unhealthy eating habits in adults may be applicable here. It has been reported, for example, that implementation intentions are only effective in relation to the achievement of a single goal (Dalton & Spiller, 2012;Verhoeven, Adriaanse, Ridder, Vet, & Fennis, 2013). We justified the inclusion of multiple plans in our intervention based on the rationale that making plans to eat healthily requires the formation of a series of related goals, and this reflects more accurately real-life goal striving, rather than a contrived focus on a single goal.…”
Section: Discussionmentioning
confidence: 99%